Severe flood probability on the middle Changjiang (Yangtze River) after completion of the Three Gorges Dam - Shankman, David; Lai, Xijun (Frontiers in Earth Science, 2022)
A major justification for building the Three Gorges Dam on the Changjiang is flood control. The dam can reduce peak discharge during severe floods. These floods, however, cannot be prevented by operation of the Three Gorges Dam alone. During the most severe floods abnormally high rainfall occurs throughout the Changjiang basin. The Three Gorges Dam can only affect discharge from the upper basin. Large tributaries on the middle Changjiang are unaffected by the dam. The cumulative impact of high discharge from large tributaries on the middle Changjiang increase flood severity with distance downstream. Also, Changjiang-lake interaction is affected by decreasing volume of Poyang and Dongting Lakes that occurred during the past few decades. These are the largest freshwater lakes in China. As a result of reduced floodwater storage capacity during summer high discharge periods, tributaries flow into the lakes with a higher base level than previously occurred. Instead of Changjiang back flowing into the lakes as previously expected during major floods, high Changjiang discharge occurs at the same time as high tributary discharge that increases peak river stage.